The concept of anatomic-functional, or biomechanical, inadequacy in traumatology and orthopaedics. Its clinical significance - Gaiko, Georgy; Brusko, Anton; Kalashnikov, Olexiy; Mayko, Vyacheslav; Kostogryz, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
On the basis of experimental and clinical investigations, a conception of anatomic-functional incongruity (AFI) of the locomotor system organs was formulated. At norm, the form and histoarchitectonics of bones and joints are conditio sine qua non for physiologic functioning of locomotor system, in whose presence a uniform distribution of mechanic stresses is provided in tissues. In AFI, whose nature is caused by consequences of injuries, inflammatory processes, disorders in the growth and development of organs and tissues of the locomotor system, the biomechanic conditions of stress change. The part of AFI in the pathogenesis of osteoarthrosis, growth disorders, pathologic reconstruction and formation of axial deformities of bones is examined.